Pengaruh Persepsi Kualitas Layanan Pelanggan dan Sistem Informasi terhadap Kinerja Organisasi Bidang Jasa - Zulkarnain, Novan (Bina Nusantara University, 2012)
Performance brings important influence to the company?s competition level to survive in free trade. Many companies started to reorganize the company's strategy to review the company's strategic objectives. Along with the development of science and technology, performance factors cannot be separated from improving service quality and information systems. The studied company is engaged in educational services and located in Tangerang. The research data was obtained through a questionnaire with 81 questions. 30 respondents were obtained by simple random sampling method. The Data from the questionnaire is used to determine the influence of the perception of customer service quality (X1) and information systems(X2) towards the performance of the organization(Y). The dimensional measurement uses SERVQUAL theory, which is tangible, reliability, responsiveness, assurance and empathy. The result shows that the equality of services and information systems in an organization influence its performance.